Survey Sarana Dan Prasarana Olahraga SD Rappocini Makassar - La Kamadi (Journal Physical Health Recreation (JPHR), 2024)
This research aims to determine the PJOK facilities and infrastructure owned by SD Rappocini Makassar including the condition, number and condition at SD Rappocini Makassar which can support the implementation of PJOK learning. This research is descriptive research using survey methods. The population in this study is all research subjects, in this case the population that will be studied in this research is the physical education, sports and health (PJOK) facilities and infrastructure at SD Rappocini Makassar. The results of this research show that the condition of the facilities and infrastructure for each sports lesson is not the same, both for football, volleyball, table tennis, athletics and gymnastics. It was concluded that of the total physical education, sports and health (PJOK) facilities and infrastructure at SD Rappocini Makassar, a percentage result was found of 41.17% which was interpreted as meeting standards and 58.82% which did not meet standards according to National Education Minister Regulation Number 24 of 2007.